Digital literacy challenges of junior high school teachers in society 5.0 education transformation - Zahara, Rizka; Niswanto, Niswanto; Rasyid, Suparta; Warni, Aida (Indonesian Research Journal in Education |IRJE|, 2026)
The development of Society 5.0 requires junior high school teachers to have adequate digital literacy to support educational transformation in the 21st century. The main problem arises when teacher competencies and school management systems are not in line with the demands of Society 5.0. This study aims to analyze the challenges of digital literacy among junior high school teachers in the context of educational transformation in the Society 5.0 era, which hinders its implementation in schools. This research uses a descriptive qualitative approach conducted at SMP Negeri 2 Sigli and SMP Unggul YPPU Sigli. Data were collected through observation, interviews, and document analysis, with the research subjects consisting of teachers and principals. The findings show that the challenges of teacher digital literacy include weak school policies, limited teacher competencies, and inadequate infrastructure. Improving digital literacy requires synergy between teacher competencies, visionary leadership, and a supportive policy framework. Recommendations include developing systematic programs, implementing continuous training, providing adequate infrastructure, and conducting indicator-based evaluations to build a digital learning ecosystem aligned with the demands of Society 5.0.